EFFECTIVE EMISSIVITY OF CLOUDS FROM RADIOMETERSONDE MEASUREMENTS AT SYOWA STATION, ANTARCTICA - ヤマモト, アキラ; ヤマノウチ, タカシ; ワダ, マコト; YAMAMOTO, Akira; YAMANOUCHI, Takashi; WADA, Makoto (National Institute of Polar Research, 1995)
P(論文) The effective emissivity of Antarctic clouds is calculated from radiation measurements using the radiometersonde in 1987 at Syowa Station, Antarctica. The accuracy of the radiometersonde near the surface is evaluated by comparison with a pyrgeometer on the ground surface. The effective emissivity is referred to vertical integrated liquid water content (LWC) from microwave radiation measurements. Though disagreement of measured volume might occur between the microwave radiometer and the sonde, the effective emissivity for downward flux correlates well to the LWC, but that for upward flux does not. A large discrepancy is found between the effective emissivity for upward flux and that for downward flux, and especially, for upward flux, the effective emissivity is very small in some cases. It is assumed that the scattering of longwave radiation by water and ice particles produces this discrepancy. The value of the LWC suggests that water particles may exist much closer to the cloud top than the cloud base. Difference among features of the effective emissivity due to type of cloud systems resolved from NOAA/AVHRR imagery is not found in this study. departmental bulletin paper